Conserved allosteric sodium in class A GPCRs: GPCR structure and allosteric effects - Katritch, Vsevolod “Seva” (Henry Stewart Talks, 2019)
GPCRs structure and function, GPCRs in human biology and pharmacology, Conserved Na+ site in class A GPCRs, Structural modification of Na+ pocket in GPCRs upon activation, Allosteric Na+ effects on agonist binding in ‘opiate’ receptors